2012
DOI: 10.3892/ol.2012.983
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic expression of p33ING1b is correlated with tumorigenesis and progression of human esophageal squamous cell carcinoma

Abstract: Abstract. p33ING1b , a newly discovered candidate tumor suppressor gene and a nuclear protein, belongs to the inhibitor of growth gene family. Previous studies have shown that p33ING1b is involved in the restriction of cell growth and proliferation, apoptosis, tumor anchorage-independent growth, cellular senescence, maintenance of genomic stability and modulation of cell cycle checkpoints. Loss of nuclear p33ING1b has been observed in melanoma, seminoma, papillary thyroid carcinoma, oral squamous cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that the transfer of p33(ING1b) protein from the nucleus to the cytoplasm may result in the loss of normal cellular function of the protein. This might play a role in tumorigenesis and lymph node metastasis of oral squamous cell carcinomas as well as esophageal squamous cell carcinoma (Zhang et al, 2008;Zhu et al, 2012). Several studies showed that nuclear import of p33(ING1b) occurs concomitantly with physical and/or functional interactions with a subset of nuclear proteins, including p53, p300/CBP, and HDAC1 in different models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the transfer of p33(ING1b) protein from the nucleus to the cytoplasm may result in the loss of normal cellular function of the protein. This might play a role in tumorigenesis and lymph node metastasis of oral squamous cell carcinomas as well as esophageal squamous cell carcinoma (Zhang et al, 2008;Zhu et al, 2012). Several studies showed that nuclear import of p33(ING1b) occurs concomitantly with physical and/or functional interactions with a subset of nuclear proteins, including p53, p300/CBP, and HDAC1 in different models.…”
Section: Introductionmentioning
confidence: 99%